Culture’s impact on entrepreneurship and interaction effect of economic development level: an 81 country study - Çelikkol, Mutlu; Kitapçi, Hakan; Döven, Gözde (Journal of Business Economics and Management, 2019)
This research has two aims. The first one is to determine how and to what extent the national cultural characteristic of a country plays a role in her entrepreneurship success. The second one is to determine whether culture and economic development levels interact with each other on influencing entrepreneurship success. A consecutive five-year longitudinal study, covering 81 countries is conducted. Longitudinal Random Effect Regression Analysis is used to determine the effects of culture on entrepreneurship rates. Data regarding the cultural dimensions indexes of the countries is obtained from Geert Hofstede website and the entrepreneurship rates from the annual reports of the Global Entrepreneurship and Development Institute. The interaction effect of cultural dimensions and economic development levels on entrepreneurship is analyzed by treating the economic development level is the interacting variable between cultural dimensions and entrepreneurship rates. Economic development levels of the countries are measured by GDP per capita, figures obtained from the World Bank. The findings are that the cultural dimensions Individualism, Long Term Orientation, and Indulgence vs. Restraint influence the entrepreneurship rate in a supportive manner, whereas Masculinity’s impact is in a rendering manner. Other dimensions seem to have no significant effect. Although relevant cultural dimensions do interact with economic development levels, their interaction effects are small. This study has several unique contributions to the entrepreneurship literature, such as its longitudinal nature, using all Hofstede Dimensions, applying a very comprehensive entrepreneurship measurement scale, its huge sample size and containing an interactive analysis of culture and economic development level which is very rare in the literature.